Analysis and design of a high temperature gas gap with tunable heat flux based on He-Ar mixture. (5th July 2019) - Ma, Mingyang; Liang, Wenfeng; Wang, Shumiao; Bai, Zhongxiong; Xie, Qilin
Highlights: A general formula was derived for gas conduction covering whole rarefaction range. Major factors affecting heat transfer processes within a gas gap were discussed. A gap was designed to measure heat transfer limit of a high temperature heat pipe. Sensitivity of heat flux dependence on pressure features by a pressure coefficient. Working states of heat pipe are divided into 2 regions of different tuning strategy. Abstract: Gas-gap-based calorimeters are very useful in thermophysical experiments where the heat flow is to be measured while keeping the cold ends of test samples at specific high temperatures. A general analytic formula for gas-mixture conduction covering the whole range of rarefaction has been derived based on fundamental equations. The major factors affecting the heat transfer process within a gas gap have been discussed. A gas gap with control strategy has been designed for heat transfer limit measurement of a high temperature heat pipe. The results show that the influence of the non-linear temperature effect of thermal conductivity is weak on the heat flux. The gas conduction is primary or even dominant within gas gaps in comparison with the thermal radiation. The sensitivity of the heat flux's dependence on the pressure can be characterized by a pressure coefficient Kp, which is a function of the composition, the temperature and the gap thickness. The possible working states of the heat pipe are found to be divided into two regions by the heat flux curve of normal-pressure Ar gap, and the tuning strategy of the heat flux based on the pressure and the composition are different in different regions.